Distribusi Geospasial Helminthiasis pada Siswa Sekolah Dasar: Studi Kasus di Kabupaten Karanganyar - Rochmadina Suci Bestari; Anjang Kusuma Netra; Restu Triwulandani Tolibin; Muhammad Firoos ‘Allaam Najmii; Maulida Rahmah (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Helminthiasis, mainly caused by Soil-Transmitted Helminths (STH), is still a health problem in Indonesia. Incidence rates vary in Indonesia, 10-90% incidence. Helminthiasis causes decrease in the nutritional status of children, children's learning concentration and anemia. The incidence of helminthiasis is particularly high among primary school-aged children, 5-13 years old. There has not been much written about the geospatial review of helminthiasis cases in Indonesia. This study aims to conduct an initial geospatial analysis and review of helminthiasis cases in students of SD Selokaton II Karanganyar. The data used were the results of helminthiasis screening which included name, address, and helminthiasis diagnosis. The diagnosis of helminthiasis was obtained from student stool samples, using direct slides, viewed under a microscope. Geospatial analysis focused on identifying clusters or spatial distribution patterns of positive cases. Of the 95 feces collected, there were 16 positive samples. The analysis showed a concentration of helminthiasis cases in the Selokaton area with hookworm and Ascaris lumbricoides as the dominant infection types. Other areas with cases were Ngargotirto, Kismoyoso and Wonorejo. Selokaton area is the area with the most cases of helminthiasis in Selokaton II Karanganyar elementary school students, and the most common types of worm infections are hookworm